Determination of Biochemical Composition in Peach (Prunus persica L. Batsch) Accessions Characterized by Different Flesh Color and Textural Typologies - Serra, Sara (Foods, 2020)
The rising interest in beneficial health properties of polyphenol compounds in fruit initiated this investigation about biochemical composition in peach mesocarp/exocarp. Biochemical evaluation of phenolic compounds and ascorbic acid were quantified through high-performance liquid chromatography (HPLC) in relation to three flesh colors (white, yellow and red) and four flesh typologies (melting, non-melting, slow softening and stony hard) within six commercial cultivars and eight breeding selections of peach/nectarine in 2007. While in 2008, quality and sensorial analyses were conducted on only three commercial cultivars (‘Big Top’, ‘Springcrest’ and ‘Ghiaccio 1’). The red flesh selection demonstrated the highest levels of phenolic compounds (in mesocarp/exocarp) and ascorbic acid. Total phenolic concentration was approximately three-fold higher in the exocarp than the mesocarp across all accessions. Breeding selections generally reported higher levels of phenolics than commercial cultivars. Flesh textural typologies justified firmness differences at harvest, but minimally addressed variations in quality and phenolic compounds. Flesh pigmentation explained variation in the biochemical composition, with the red flesh accession characterized by an abundancy of phenolic compounds and a high potential for elevated antioxidant activity. Sensorial analyses ranked the cultivar with high soluble solids concentration:titratable acidity (SSC:TA) and reduced firmness the highest overall. Red flesh is a highly desirable trait for breeding programs aiming to improve consumption of peaches selected for nutraceutical properties.